Estudio bioquímico y nutricional del extracto liofilizado del fondo de alcachofa Cynara scopolymus - Aguilar G., Selma (2000)
The aim of the present study is to obtain a protein concentrate from fresh artichoke heart and to determine the amount and quality of protein present. For this reason we employed different extractions in order to obtain acidic, aqueous and alcoholic concentrates with three different alcoholic values, obtaining 13,41g/100g yield of eatable protein with the 86% alcoholic extract, deterrnined by Kjeldahl method, The extracted samples were analyzed by PAGE - SDS electrophoresis, Laemmli method using a 12,5% polyacrilamide concentration, and we found it contained a reduced number of protein bands (between 8 and 10), being the most abundant the ones with Molecular Mass of 24 000, 29 000 and 36 000 Daltons,The amino acid content of lyophilized artichoke heart in the 86% alcoholic concentrate was deterrnined by HPLC, finding that the limiting amino acids were lysine and leucine, being valine and methionine the ones that showed the higher values. The nourishing evaluation of artichoke proteins by essential amino acid count indicates that this vegetable partially covers the essential amino acid necessities recommended by FAO/OMS/ONU for children.